Greener energy for ocean transportation - Lim, Rachel Rui Qian (Nanyang Technological University, 2021)
This report will study the feasibility of the adoption of alternative greener marine fuels in the maritime industry. The increased focus on the maritime transport industry to lower carbon emissions to combat climate change has resulted in greater regulatory emphasis by international bodies. Three fuels – Liquefied Natural Gas (LNG), biofuels and hydrogen, will be considered in this study. Where the environmental benefits, infrastructure availability, economic viability, technological and regulatory factors compared to Heavy Fuel Oil (HFO) will be taken into consideration. The feasibility of substantial adoption of LNG will be evaluated and compared to the other fuels mentioned. This study would then be concluded with an overview of the maritime industry’s efforts in decarbonization.